The Relationship of Perception, Distance of Health Facilities and Husband's Support with Mother's Compliance with Immunization of its Baby According to Schedule in Sidetapa Village - Putu Puriadi; Asep Arifin Senjaya; Ni Ketut Somoyani (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Immunization is an effort to actively create immunity against adisease so that when exposed to the disease they do not get sick.The purpose of the study was to determine the relationshipbetween perception, distance of health facilities, husband'ssupport with mother's compliance in bringing her baby'simmunization according to schedule. The type of research isquantitative observational analytic, cross-sectional design. Totalsampling of 46 mothers who have babies aged 9-12 months,questionnaire data collection tools, univariate analysis andbivariate analysis. The results of the Spearmen Rank test analysisof the relationship between perception and immunizationcompliance with values (p: 0.009), (r: 0.380) showed a weakpositive relationship. Distance of health facilities with values (p:0.026), (r: 0.328) showed a weak positive relationship, andhusband's support with values (p: 0.000), values (r: 0.569)showed that husband's support had a moderate positiverelationship. The conclusion of the study is that there is arelationship between perception, distance from health facilitiesand husband's support with mothers' compliance in bringing theirbabies' immunizations according to the schedule in SidetapaVillage in 2024. Suggestions for mothers are expected to complywith their babies' immunizations according to recommendationsto avoid diseases that can be prevented by immunization.